Arbitrary movement simulation using 3D NC-FVM for electromagnetic problems. Issue 4 (2nd July 2018) - Amrani, Ishaq; Cheriet, Ahmed; Feliachi, Mouloud
Abstract : Purpose: The purpose of this paper is to propose to simulate an arbitrary movement in electromagnetic problems by means of a 3D nonconforming finite volume method (NC-FVM). The moving part can be displaced according to the x, y and/or z direction. Design/methodology/approach: The 3D nonconforming mesh technique coupled to the FVM is used to handle arbitrary displacement of moving parts. Accordingly, the whole problem domain is divided into two parts: moving part and fixed part. Both parts are meshed independently. By using a suitable connection between both fixed and moved meshes, the movement can be performed according to the three axes. Findings: The TEAM Workshop Problem No. 23 is used to test the proposed method. The calculated values of the magnetic force applied to the permanent magnet for different positions of the magnet show the efficiency of the proposed method. Originality/value: This paper introduces the NC-FVM to solve electromagnetic problems which contain moving parts. Here, the movement can be performed according to the three axes.